Family identity in the digital sphere: Mothers’ narratives on public and private Instagram accounts - Widiastiana Vista Wijaya; Tuti Widiastuti; Dinda Rakhma Fitriani (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2025)
This study examines the ways Indonesian mothers construct and negotiate family identity through the use of public and private Instagram accounts. The growing presence of mothers on Instagram has transformed the representation of family life into a performative digital practice shaped by visibility, social interaction, and cultural norms. Rather than functioning as a neutral record of everyday experiences, Instagram has become a discursive space where family identity is strategically produced and managed. Drawing on Narrative Performance Theory, this qualitative research employs in-depth interviews with Indonesian mothers who engage in different patterns of digital visibility. The findings indicate that mothers with public Instagram accounts tend to construct curated narratives of family harmony and ideality to achieve social recognition, legitimacy, and broader audience engagement. In contrast, mothers who use private accounts emphasize maternal reflexivity, emotional closeness, ethical responsibility, and the protection of children’s digital privacy. These contrasting narrative practices demonstrate that digital family identity is shaped through internal and external boundary management strategies that balance self-expression, social connection, and digital safety. The study highlights Instagram’s role as a dynamic arena in which family identity is continuously performed, negotiated, and redefined, contributing to broader discussions on digital parenting, family communication, and ethical considerations in social media use.